Extracellular Vesicles Transfer the Receptor Programmed Death-1 in Rheumatoid Arthritis - Greisen, Stinne R.; Yan, Yan; Hansen, Aida S.; Venø, Morten T.; Nyengaard, Jens R.; Moestrup, Søren K.; Hvid, Malene; Freeman, Gordon J.; Kjems, Jørgen; Deleuran, Bent (Frontiers in Immunology, 2017)
Introduction: Extracellular vesicles (EVs) have been recognized as route of communication in the microenvironment. They transfer proteins and microRNAs (miRNAs) between cells, and possess immunoregulatory properties. However, their role in immune mediated diseases remains to be elucidated. We hypothesized a role for EVs in the rheumatoid arthritis (RA) joint, potentially involving the development of T cell exhaustion and transfer of the co-inhibitory receptor programmed death 1 (PD-1). Methods: Synovial fluid mononuclear cells (SFMCs) and peripheral blood mononuclear cells (PBMCs) from RA patients were investigated for PD-1 and other markers of T cell inhibition. EVs were isolated from RA plasma and synovial fluid. In addition, healthy control (HC) and RA PBMCs and SFMCs were cultured to produce EVs. These were isolated and investigated by immunogold electron microscopy (EM) and also co-cultured with lymphocytes and PD-1 negative cells, to investigate their functions. Finally, the miRNA expression profiles were assessed in EVs isolated from RA and HC cell cultures. Results: Cells from the RA joint expressed several T cell co-inhibitory receptors, including PD-1, TIM-3 and Tigit. ELISA demonstrated the presence of PD-1 in EVs from RA plasma and synovial fluid. Immunogold EM visualized PD-1 expression by EVs. Co-culturing lymphocytes and the PD-1 negative cell line, U937 with EVs resulted in an induction of PD-1 on these cells. Moreover, EVs from RA PBMCs increased proliferation in lymphocytes when co-cultured with these. All EVs contained miRNAs associated with PD-1 and other markers of T cell inhibition, and the content was significantly lower in EVs from RA PBMCs than HC PBMCs. Stimulation of the cells increased the miRNA expression. However, EVs isolated from stimulated RA SFMCs did not change their miRNA expression profile to the same extend. Conclusion: EVs carrying both the PD-1 receptor and miRNAs associated with T cell inhibition were present in RA cell cultures. Upon stimulation, these miRNAs failed to be up-regulated in EVs from RA SFMCs. This was in line with increased expression of T cell co-inhibitory markers on SFMCs. In conclusion, we suggest EVs to play a significant role in the RA microenvironment, potentially favoring the progression of T cell exhaustion.